Pengaruh Kecenderungan Mengambil Risiko, Ekspektasi Pendapatan, dan Kecerdasan Adversitas Terhadap Intensi Berwirausaha - Hutama, Revanza Harviananda; Achsa, Andhatu; Ikhwan, Khairul (DPPM Universitas Pelita Bangsa, 2024)
This research is motivated by the phenomenon that every year universities in Indonesia produce new graduates who continue to increase in number. This condition results in more competitive employment opportunities. Problems regarding the unemployment rate and the proportion of employment also continue to increase. According to BPS in 2022, the open unemployment rate at the Diploma education level was 4.59% and 4.80% for college graduates. This study aims to determine the effect of risk-taking tendencies, income expectations, and adversity intelligence on entrepreneurial intentions in 2019 Management undergraduate students at Tidar University. This study uses a quantitative approach that uses a questionnaire as a data collection instrument. The sample in this study were 56 S1 Management 2019 students of Tidar University using purposive sampling technique with the slovin formula. The data analysis technique used in this research is multiple linear regression analysis, t test, F test, and coefficient of determination test. From the results of the analysis test conducted, the results show that the tendency to take risks and adversity intelligence has no effect on entrepreneurial intention. However, income expectations have a positive and significant effect on entrepreneurial intention.